2021
DOI: 10.3390/cells10040921
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Biased lncRNA Signature in Fetal Growth Restriction (FGR)

Abstract: Impaired fetal growth is one of the most important causes of prematurity, stillbirth and infant mortality. The pathogenesis of idiopathic fetal growth restriction (FGR) is poorly understood but is thought to be multifactorial and comprise a range of genetic causes. This research aimed to investigate non-coding RNAs (lncRNAs) in the placentas of male and female fetuses affected by FGR. RNA-Seq data were analyzed to detect lncRNAs, their potential target genes and circular RNAs (circRNAs); a differential analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…Transcriptome profiling was performed as previously described [ 33 , 34 , 35 ]. Briefly, to obtain the stringent results of differentially expressed transcribed active regions (DE-TARs), the count gene expression matrix was calculated by the ballgown statistical method [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptome profiling was performed as previously described [ 33 , 34 , 35 ]. Briefly, to obtain the stringent results of differentially expressed transcribed active regions (DE-TARs), the count gene expression matrix was calculated by the ballgown statistical method [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…lncRNA has been detected in diverse tissues, including placenta, and altered expression of lncRNAs has been demonstrated in pregnancy-speci c diseases, such as recurrent pregnancy loss, preeclampsia, fetal growth restriction and gestational diabetes mellitus [18][19][20][21]. Some research has shown the differential expression of lncRNA pro le in the placenta complicates with fetal growth restriction [22]. However, it is still unknown whether differential expression of placental lncRNA contributes to the pathogenesis of sIUGR.…”
Section: Introductionmentioning
confidence: 99%